Probing the Gas Fueling and Outflows in Nearby AGN with ALMA - Audibert, Anelise; Combes, Françoise; García-Burillo, Santiago; Salomé, Philippe (Frontiers in Astronomy and Space Sciences, 2017)
Feeding and feedback in AGN play a very important role to gain a proper understanding of galaxy formation and evolution. The interaction between activity mechanisms in the nucleus and its influence in the host galaxy are related to the physical processes involved in feedback and the gas fuelling of the black hole. The discovery of many massive molecular outflows in the last few years have been promoting the idea that winds may be major actors in sweeping the gas out of galaxies. Also, the widely observed winds from the central regions of AGN are promising candidates to explain the scaling relations (e.g. the black hole-bulge mass relation, BH accretion rate tracking the star formation history) under the AGN feedback scenario. Out goal is to probe these phenomena through the kinematic and morphology of the gas inside the central kpc in nearby AGN. This has recently been possible due to the unprecedented ALMA spatial resolution and sensitivity. We present results on NGC7213 and NGC1808, the latter is part of a new ALMA follow-up of the NuGa project, a previous high-resolution (0.5-1”) CO survey of low luminosity AGN performed with the IRAM PdBI.